Utility of Volumetric Measurement via Weight-Bearing Computed Tomography Scan to Diagnose Syndesmotic Instability. (July 2020) - Bhimani, Rohan; Ashkani-Esfahani, Soheil; Lubberts, Bart; Guss, Daniel; Hagemeijer, Noortje C.; Waryasz, Gregory; DiGiovanni, Christopher W.
Background: Weight-bearing computed tomography (WBCT) allows evaluation of the distal syndesmosis under physiologic load. We hypothesized that WBCT volumetric measurement of the distal syndesmosis would be increased on the injured as compared to the contralateral uninjured side and that these 3-dimensional (3D) calculations would be a more sensitive determinant than 2-dimensional (2D) methodology among patients with syndesmotic instability. Methods: Twelve patients with unilateral syndesmotic instability requiring operative fixation who underwent preoperative bilateral foot and ankle WBCT were included in the study group. The control group consisted of 24 patients without ankle injury who underwent similar imaging. On WBCT scan, 2D measurements of the syndesmosis joint were first measured 1 cm above the joint line in the axial plane via syndesmotic area and distances between the anterior, middle, and posterior quadrants. Thereafter, comparative 3D volumetric measurements of the syndesmotic joint were also calculated: (1) from the tibial plafond extending until 3 cm proximally, (2) 5 cm proximally, and (3) 10 cm proximally. Results: In patients with unilateral syndesmotic instability, all 3 weight-bearing volumetric measurements were significantly larger on the injured side as compared to the contralateral, uninjured side ( P < .001). In the control group, there was no difference between syndesmotic volumes at any level. Of these 3 anatomic reference points, the 3D measurement spanning from the tibial plafond to a level 5 cm proximally had the highest relative volumetric ratio between the injured and uninjured side, suggesting it is the most sensitive in distinguishing between stable and unstable syndesmotic injury ( P < .001). Notably, this 3D volumetric measurement was also more sensitive than 2D measurements ( P = .001). Conclusion: 3D volumetric measurement of the syndesmosis joint appears to be the most effective way to diagnose syndesmotic instability, compared with more traditional 2D syndesmosis measurement. Level of Evidence: Level III, retrospective comparative study.